A case of spontaneous urinary bladder rupture secondary to urinary retention due to an urethral stricture - Palthe, S. (Urol Case Rep, 2018)
A spontaneous, non-traumatic, urinary bladder rupture is a rare condition. We describe a case of a 23-year-old male with a spontaneous bladder rupture secondary to urinary retention, due to an urethral stricture. He presented to the emergency department with voiding difficulties, severe abdominal pain and renal failure. Abdominal ultrasound revealed large amounts of ascites. After an unsuccessful attempt to place a Foley catheter a cystoscopy was performed which showed an urethral stricture. On CT-cystogram an intra-peritoneal bladder rupture was diagnosed and the patient underwent laparoscopic repair of the bladder wall. The postoperative course was uneventful.